TINJAUAN KINERJA PERBANKAN INDONESIA TERHADAP STABILITAS SISTEM KEUANGAN - Wienna Meidy Utami; Anas Iswanto; Mirzalina Zaenal (Jurnal Ekonomika dan Dinamika Sosial, 2025)
This study aims to analyze the effect of banking performance on banking stability in Indonesia. The data used is time series data from 2008-2021. However, before conducting an analysis using time series data, the Z-Score formula is used to calculate the variable size of bank stability. The results of this study indicate a significant effect of banking performance on banking stability in Indonesia. Keywords: Banking Performance, Banking Stability, Z-Score